Intermediate Robot Building, Second Edition - Cook, David (Apress, 2012)
Greetings robot builder! Over the years, I’ve created many homemade robots (some of which, only the builder could love). However, with each successive robotic generation, I try to gradually expand my knowledge of electronics, mechanics, machining, software, and art by experimenting with new techniques, features, or parts (keeping in mind, all the time, it’s a hobby to be enjoyed). Rarely will my latest robot be composed entirely of new technologies. Instead, each robot takes a small evolutionary step with a few changes from a collection of tried-and-true modules. In a self-contained way, this book follows that trend by tracing the stages of growth of a single robot, named Roundabout, from mindless prototype to virtuoso. My approach is to delve deeply into a particular part or subject, rather than skimming the surface of an entire design. This focus on modules and segments allows you to create your own personalized robot from desired pieces, rather than necessarily replicating exactly what I’ve made. I invite you, now, into my laboratory (straight through the living room, turn left at the kitchen) for friendly conversations about robot secrets and designs.